Thoracic aortic aneurysm in pregnancy: morphological analysis of 6 cases - V. P. Zakharova; S. O. Siromakha; J. W. Roos-Hesselink; V. I. Kravchenko; Yu. V. Davydova; V. V. Lazoryshynets (Patologìâ)
Aortic dissection is rare but life-threatening complication in pregnancy, causing significant maternal and perinatal losses. Pregnancy may influence the integrity of the vessel wall and is a risk factor for dissection. There are very few data in the literature on structural changes in the aortic walls during pregnancy complicated by aortic dissection.